CYBER OFFENSE AS A THREAT TO ECONOMIC SECURITY OF UKRAINE - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the objective factors arising from the specificity of cybercrime, threats and their negative impact on the economic security of the state are considered, criminal offenses in the field of bank payment cards are characterized, features that distinguish cybercrime from other criminal offenses, the definition of «cybercrime» a cyber security system that must be based on certain principles, objects and entities that provide it. Methods: the study was conducted using methods such as analysis, synthesis, comparison. Results: it is concluded that cybercrime poses a threat to Ukraine’s economic security, so measures are taken at the legislative level to prevent and counteract such manifestations. Discussion: cybersecurity issues and prevention of cybercrime in the economic sphere. The widespread use of modern information technology in economic relations puts the solution of problems of economic security of society in the first place. Currently, the number of offenses committed in the industry is increasing in proportion to the number of users of computer networks. Such growth is an inevitable process for both the development of information technology and the improvement of the professionalism of offenders in the sphere of economic relations. In Ukraine, measures are being put in place at the legislative level to ensure cybersecurity in all spheres of society, including in the economic sphere. The manifestations of criminal use of high information technologies in the economic security of society is one of the main directions of counteracting cybercrime in the country. Cybersecurity should be an ongoing process for the activities of relevant government agencies to prevent and counteract cyberspace threats to Ukraine. It should be based on the principles of: the rule of law; ensuring the balance of rights and interests of a person, citizen, state; interaction between government agencies and the public. On the basis of the foregoing, we propose to identify cybercrime in the field of economic security as a system of cybercrime that encroaches on vital public relations in the economic sphere using computer systems and computer technologies.